PEL 2021
DOI: 10.7764/pel.58.2.2021.4
|View full text |Cite
|
Sign up to set email alerts
|

PDF PDF (English) HTML HTML (English) Vocabulario académico y habilidades de lenguaje académico: predictores de la comprensión lectora de estudiantes de primaria y secundaria en México

Abstract: Investigaciones previas han encontrado que las habilidades del lenguaje académico predicen positivamente los resultados de comprensión de lectura en español de los adolescentes hispanohablantes más allá del conocimiento del vocabulario académico. Este estudio examina la contribución específica del vocabulario académico y de las habilidades de lenguaje académico a la comprensión lectora de estudiantes de primaria y secundaria en el noreste de México. Participaron en el estudio un total de 1103 estudiantes de es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 25 publications
(38 reference statements)
1
1
0
14
Order By: Relevance
“…Recent studies have found that students’ CALS predict reading comprehension in English-speaking students in Grades 4 to 8, above and beyond word-level reading fluency, vocabulary knowledge, and student sociodemographic factors, for students designated as English proficient or English learners (Barr et al, 2019; Phillips Galloway & Uccelli, 2019b; Uccelli et al, 2015). Consistent findings have been reported in studies that examined students’ CALS as predictor of reading comprehension in Spanish-speaking samples in multiple Latin American countries, including Chile, Colombia, Mexico, and Perú (Meneses et al, 2017; Romero et al, 2021) and in Portuguese in Brazil. Aligned with prior research conducted in English, these studies on Spanish or Portuguese CALS have found consistently that CALS predict reading comprehension, even when controlling for basic word recognition skills, vocabulary knowledge, and sociodemographic factors.…”
Section: Language and Reading Relations Throughout Mid-adolescencesupporting
confidence: 82%
“…Recent studies have found that students’ CALS predict reading comprehension in English-speaking students in Grades 4 to 8, above and beyond word-level reading fluency, vocabulary knowledge, and student sociodemographic factors, for students designated as English proficient or English learners (Barr et al, 2019; Phillips Galloway & Uccelli, 2019b; Uccelli et al, 2015). Consistent findings have been reported in studies that examined students’ CALS as predictor of reading comprehension in Spanish-speaking samples in multiple Latin American countries, including Chile, Colombia, Mexico, and Perú (Meneses et al, 2017; Romero et al, 2021) and in Portuguese in Brazil. Aligned with prior research conducted in English, these studies on Spanish or Portuguese CALS have found consistently that CALS predict reading comprehension, even when controlling for basic word recognition skills, vocabulary knowledge, and sociodemographic factors.…”
Section: Language and Reading Relations Throughout Mid-adolescencesupporting
confidence: 82%
“…These cross-disciplinary resources have a receptive dimension (understanding how the resources work) and a productive dimension (using resources in constructing texts). Studies shown the significant contribution of receptive cross-disciplinary language skills to reading comprehension in both English (Uccelli et al, 2015) and Spanish among middle school students (Meneses, Uccelli, et al, 2018;Romero-Contreras et al, 2021) as well as the quality of school genre writing (e.g., Figueroa et al, 2018).…”
Section: The Role Of Disciplinary and Cross-disciplinary Language Ski...mentioning
confidence: 99%
“…La comprensión lectora puede ser definida tomando en cuenta diversos enfoques. Algunos de ellos consideran las habilidades particulares de los lectores (Catalá et al, 2001;Jiménez, 2014;Rello, 2017;Romero-Contreras et al, 2021), otros ponen el énfasis en los procesos cognitivos que se desarrollan (Durán et al, 2018), y otros son más integrales, al considerar varios elementos para definirla (Bustos et al, 2021;Cairney, 2018).…”
Section: Marco Teóricounclassified